Kontribusi Ibu Rumah Tangga Dalam Meningkatkan Perekonomian Keluarga Melalui Berdagang Online Selama Pandemi Covid-19 di Kecamatan Sambas - U. Sulia Sukmawati; Ahmad Yasir; Neli Neli (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2021)
This study aims to determine the level of housewives' contribution to the family economy and how housewives do online trading in an Islamic perspective. In this study using a qualitative approach, with a total of 30 respondents who resided in Sambas District, Sambas Regency. The results showed that most of the housewives contributed greatly to increasing family income, with a contribution rate of more than 30% as many as 19 people and during the pandemic the number of housewives who contributed more than 30% decreased only around 17 people out of 30 respondents. The reason for housewives to trade online is mostly due to filling spare time and helping family income. Online trading carried out by housewives does not violate Islamic law, because online trading is carried out part time, so it does not leave its main obligation, namely as a wife and mother at home, and overall get permission from the husband. As for the Akad and transactions carried out by 30 respondents based on the principle of honesty, every product advertised on social media is described in detail